Intergenerational transmission of risk attitudes - A revealed preference approach - Necker, Sarah; Voskort, Andrea (European Economic Review, 2014)
This study investigates whether children and parents show a similar willingness to take risk in their choice of occupation. Using data from the German Socio-Economic Panel, we calculate the occupational variation in earnings unexplained by human capital differences to obtain a measure of occupational risk. We find that fathers' earnings risk is significantly positively related to sons' earnings risk. The same link is found when unemployment risk is considered. However, a conclusion indicated by previous studies based on self-reports of individuals' risk attitude as well as our findings is that intergenerational transmission is weak in terms of effect size. © 2013 Elsevier B.V.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Intergenerational transmission; Occupational choice; Risk preferences